x'' + x = 0
"\\frac {d^2x}{dt^2} + x = 0"
Let x = emt be a solution
So m²emt+ emt = 0
=> emt(m²+1) = 0
Auxiliary equation is m²+1=0 as emt ≠0
=> m = ±i
So the general solution of the given differential equation is
x = (C1 cost + C2 sin t)e0*t
=> x = C1 cost + C2 sin t
Differentiating with respect to t
"\\frac {dx}{dt}" = - C1 sin t + C2 cos t
Using the initial conditions
x = "\\frac {\u221a3}{2}" when t = "\\frac {\u03c0}{3}"
"\\frac {dx}{dt}" = 0 when t = "\\frac {\u03c0}{3}"
So C1 cos("\\frac {\u03c0}{3}" ) + C2 sin("\\frac {\u03c0}{3}" ) = √3/2
=> "\\frac {1}{2}" C1 + "\\frac {\u221a3}{2}" C2 = "\\frac {\u221a3}{2}"
=> C1+ √3C2 = √3 -----------eq(1)
Again "\\frac {dx}{dt}" = 0 when t = "\\frac {\u03c0}{3}"
So,. - C1 sin("\\frac {\u03c0}{3}" ) + C2 cos("\\frac {\u03c0}{3}" ) = 0
=> - "\\frac {\u221a3}{2}" C1 + "\\frac {1}{2}" C2 = 0
=> -√3C1 + C2 = 0
Multiplying by √3
-3C1 + √3C2 = 0 --------------eq(2)
Subtracting eq(2) from eq(1) we get
4C1 = √3
So C1 = "\\frac {\u221a3}{4}" and hence C2 = √3C1= "\\frac {3}{4}"
So the actual solution is
x = "\\frac {\u221a3}{4}" cos t + "\\frac {3}{4}" sin t
Comments
Leave a comment